2013
DOI: 10.9721/kjfst.2013.45.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-adipogenic Effects of PineXol®

Abstract: Pine bark extract is made from the bark of Pinus densiflora which naturally contains occurring phytochemicals such as phenolic compounds. PineXol ® from products of pine bark extract is sold under the brand name. The aim of this study was to evaluate the total phenol, total flavonoids contents and antioxidant activity of the PineXol ® as well as to assess the lipid accumulation during adipogenesis of 3T3-L1 cells. Our results demonstrate that the total phenolic and flavonoids contents of the PineXol ® were 717… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
3
12
1
Order By: Relevance
“…It is in accordance with the above given scope that PineXol (PX) (Nutrapharm Co., Korea), extracted from Korean Red Pine (Pinus densiflora) bark, has been reported to have similar beneficial functions to pycnogenol, including antioxidant, anti-inflammation, and anti-lipogenic effects in vitro [28,29]. According to HPLC analysis, because the phenolic compounds (catechin and taxifolin) and flavonoid (procyanidin B1 and B2) contents are comparable, the similarity of PX and Pycnogenol composition is high [30,31].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…It is in accordance with the above given scope that PineXol (PX) (Nutrapharm Co., Korea), extracted from Korean Red Pine (Pinus densiflora) bark, has been reported to have similar beneficial functions to pycnogenol, including antioxidant, anti-inflammation, and anti-lipogenic effects in vitro [28,29]. According to HPLC analysis, because the phenolic compounds (catechin and taxifolin) and flavonoid (procyanidin B1 and B2) contents are comparable, the similarity of PX and Pycnogenol composition is high [30,31].…”
Section: Introductionsupporting
confidence: 67%
“…The PX 75 μg/ml and PX 100 μg/ml treatment groups showed a decline in lipid accumulation by approximately 36% and 40%, respectively, in comparison with the CTL group (p < 0.05). Lipid accumulation in the PX-treated groups (50, 100, and 200 μg/ml) was considerably more inhibited than in the control group for 3T3-L1 [29]. Western blot analysis for proteins related to adipogenesis was conducted to examine the given mechanism.…”
Section: Lipid Accumulation Reduction In 3t3-l1 Adipocytes By Pxmentioning
confidence: 99%
“…Levels of C/EBPα, PPARγ, and perilipin were clearly suppressed in the PineXol-treated groups, suggesting that PineXol could be used to prevent obesity. Previous studies have reported similar antilipogenic effects in vitro: PineXol and Pycnogenol, for example, both inhibit lipid accumulation in 3T3-L1 adipocytes [16,23]. Pycnogenol decreases the levels of perilipin A and H89 (a PKA inhibitor) in both ob/ob mice and primary adipocytes [21].…”
Section: Discussionmentioning
confidence: 59%
“…PineXol (Nutrapharm Co., Korea), extracted from the bark of Korean red pine (Pinus densiflora), has been reported to have similar beneficial effects, including antioxidant, antiinflammatory, and antilipogenic activities in vitro [22,23]. The composition of PineXol is similar to that of Pycnogenol, with comparable phenolic compounds (catechin and taxifolin) and flavonoids (procyanidin B1 and B2), according to HPLC analyses [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, excessive ROS generation is associated with increased lipid accumulation during adipocyte differentiation ( 33 , 34 ). Previous studies reported excessive differentiation of 3T3-L1 cells induced by transition metals (Cu 2+ or Fe 2+ ), due to increased expression of adipogenic transcriptional factors related to the NADPH-dependent H 2 O 2 -generating system ( 35 ). Thus, we investigated the inhibitory effect of WGE and F-WGE treatment on adipogenesis in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%